ENT 530 Social Media Portfolio: BeauTyra / Siti Su'aidah Kaiyisah Sharuddin - Sharuddin, Siti Su'aidah Kaiyisah (2021)
BeauTyra is a local Malaysian beauty brand that is own by Tyra Kamaruzzaman. This brand aims to make affordable beauty products so everyone can grab them and wear them to be beautiful every day. They are a brand that also celebrates diversity in women with all different body shapes, sizes, and skin. Establish in the year 2018, this brand kicked off with their famous set of blushers call "Born to Blush". Due to their photoshoot campaign to promote the product, it sold out within a few minutes of launching. The Born to Blush set consists of Mermaid, Feline, Cottontail, and their limited edition blushers call Mariposa and Unicorn. Now, Beautyra has expanded its product line to lipsticks, eyeshadow pallets, and hair-to-toe mists. Their latest release is the Baddie Collection with four different lipstick shades. Beautyra is a famous brand due to its campaigns that celebrate all kinds of beauty in Malaysia that capture its heart. Their products are available to purchase from their official website, Shopee, or even from their Beaubosses that is available all over Malaysia and most of the world. Beautyra is a local brand that has a very big potential and can go far in the beauty industry.